Timing of Probing for Congenital Nasolacrimal Duct Obstruction - Khwaja Khalid Shoaib, Zia ul Islam, Zia Muhammad, Muhammad Tariq (Pakistan Journal of Ophthalmology, 2018)
Purpose: To study the outcome of conservative treatment and of probing and irrigation in congenital naso-lacrimal duct obstruction in infants and children. Material and Methods: Eighty one eyes of 63 patients were studied. Children were divided into three groups. Group I included infants from 0-6 months, group II included infants from 7 – 12 months and group III included infants above one year. Results: In group I out of 38 patients, 35 (55.5%) were relieved of symptoms of epiphora and discharge with conservative treatment. In group II, out of 17 infants, 11 (17.4) were relieved of symptoms with conservative treatment. In group III, only one patient (1.58%) out of 9P responded to conservative treatment. Conclusion: Spontaneous resolution of naso-lacrimal duct obstruction occurs in most of the cases with conservative treatment and massage. In the remaining patients not responding to the conservative approach, probing and irrigation is successful in the majority of infants.